THE RELATIONS BETWEEN FISCAL AND MONETARY POLICY IN STATE BUDGET MANAGEMENT IN INDONESIA ACCORDING TO ABU UBAID AL QASIM BIN SALAM - Syamsuri Syamsuri; Adinda Muftiviany Nur Jamilah (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2020)
The study aim to analyze fiscal and monetary policy in the management of indonesia's state budget according to Abu Ubaid Al-Qasim. This research takes the form of a historical figure, namely historical research on one of the lives of a person that includes ideas, thoughts, as well as influential things in the formation of his thoughts. Thus the method used in this study is the library (research Library) with the object of research is Abu Ubaid Al-Qasim about his thoughts on the economic development of Islam, which is analyzed from his work al-Amwal. To obtain data through In this research, the primary data collection is carried out by anlyzing journal, and some books which reevan to this research. The result of this study is that fiscal and monter policy that runs in Indoensia in managing the State Budget is considered not to be running effectively and has not been able to solve the problem of the State because the system used contains usury. Thus, the mechanism of conformity according to Islam from abuubaid's view brings the right solution that the instrument is like zakat, jizyah, khumus, kharaj into a very effective management instrument of state budget and finance because the proper allocation according to the needs of the State and does not contain usury. Research Limitations of this research is limited by examining how fiscal and monetary policy in managing finance and state budget according to Abu Ubaid Al-Qasim in his Book al-Amwal by looking at the phenomena of financial management centered in BaitulMaal during the time of Prophet Muhammad and his caliphs.